Pengembangan Modul Pembelajaran IPA Berbasis PjBL-STEM untuk Meningkatkan Kemampuan Berpikir Kreatif pada Materi Pencemaran Lingkungan - Destama Einstean Shodiq; Muzzazinah; Prabang Setyono (Jurnal Penelitian Pendidikan IPA, 2025)
PjBL-STEM is a project-based learning model integrated with Science, Technology, Engineering and Mathematics (STEM). The study developed a PjBL-STEM-based science module to improve creative thinking skills. The type of research and development used is ADDIE, namely analysis, design, development, implementation, evaluation. The feasibility of the module uses expert validation consisting of 3 material experts, 4 media experts, and 3 language experts. The module's practicality test by teachers consists of 4 teachers, and the readability test consists of 32 students. The module's effectiveness test uses a quasi-experiment with control and experimental classes. The control class is in VII C and the experimental class is in VII D. In each class there are 32 students with 16 females and 16 males. Based on the results of the study, it can be concluded that the average results of the validation of material experts (0.89), media experts (0.90), and language experts (0.86). Practicality by teachers (96%) and module readability (90%). The N-Gain value is 0.57 with a moderate category, which means that this module is quite effective in improving students' creative thinking skills.